Agricultura urbana e práticas sociais inovadoras para sustentabilidade: estudo de caso de uma horta comunitária de Curitiba (PR) - Angelo, Cristiane Longhi de (2018)
Facing sustainability challenges, broader changes and new directions are required. In the dynamics of social life, many changes occur incessantly through innovations, taking into account the active participation of civil society and its mobilizing actions. For example, the community-based urban farming, activity that promotes public health, social development, financial self-sufficiency, qualification, and high level of governance, wich articulates with companies and governamental agencies in a common effort towards sustainability. In this context, this study was interested in investigating the innovative practice of community garden in Curitiba (PR), specially the Rio Verde Garden initiative, internationally awarded in 2016 as an example of urban resilience. The interest was following the urban farmers routine and raise elements to understand the dynamics of social transformations such as the urban agriculture initiatives. As the theoretical basis, this study was supported by the approaches of the Theory of Social Practice and Innovation for Sustainability, this one through the Multi-level Perspective of Sociotechnical Transitions. The main purpose was to understand the interaction focused on sustainability, the units of analysis, that were social practice of community garden and sociotechnical systems, were simultaneously looked at their interaction and the dynamics of sustainable innovations. The research adopted the qualitative approach, with a case study strategy. In the field research, the methods such as participant observation and narrative interviews were taken as advantage, considering the researcher depth and proximity with the analysis object and allowed to grasp practice interconnected elements, as well as the methods of analysis were the itinerary of practices and narrative analysis. In this regard, the narrative was presented in the results discussion, when analyzing the practices, considering the practioners actions and sayings, under the researcher's perspective. The reality investigated revealed the interaction of farming practice with the dynamics of 2 sociotechnical systems, which are the Gastronomy, with a dynamics of niche innovations, where there are sustainable initiatives for growing organic food, social Technologies, farming with organic waste, and as an alternative supply to restaurants; and the Public Administration and Governance, with civil society mobilizations, such as gaining permission to grow food in public spaces. When intersecting with other activities and rules, the farming practice ended up reflecting its characteristics and performance in the dynamics of the socio-technical systems identified. In particular, five innovative practice-arrangement bundles were identified, two with the Gastronomy system and three with the Public Administration and Governance System, and it was found that the intersection provided a favorable context for changes in related systems, such as experimentation atmosphere or as a trigger for niche initiatives. In terms of the effects in practice, new understandings, rules and activities were identified, and growing food in a common area assumed other meanings and motivations. It was found that it is not advisable to integrate or merge the two theoretical approaches, yet the simultaneous, though challenging, look reveals the complexity with which urban farming and social practices make up to sustainable transformations.